2017
DOI: 10.1128/jvi.01866-16
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide Inhibits Porcine Reproductive and Respiratory Syndrome Virus Replication by the Cyclic GMP/Protein Kinase G and NF-κB Signaling Pathway

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) causes significant economic losses to the pork industry worldwide each year. Our previous research demonstrated that heme oxygenase-1 (HO-1) can suppress PRRSV replication via an unknown molecular mechanism. In this study, inhibition of PRRSV replication was demonstrated to be mediated by carbon monoxide (CO), a downstream metabolite of HO-1. Using several approaches, we demonstrate that CO significantly inhibited PRRSV replication in both a PRRSV per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 63 publications
(74 reference statements)
4
38
0
Order By: Relevance
“…NF‐κB is a transcription factor playing a key role in inflammation, and several studies have demonstrated that it is regulated by the NO/cGMP/PKG signaling pathway . Therefore, we analyzed the phosphorylation of NF‐κB p65 subunit in the nuclear fraction of Molt‐3 cells treated with tadalafil/Sp‐8‐Br‐PET‐cGMP by Western blot analysis, which revealed that phospho‐NF‐κB p65 was downregulated by the drugs, but PKG inhibitor KT5823 (100 nM) reversed the effect (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…NF‐κB is a transcription factor playing a key role in inflammation, and several studies have demonstrated that it is regulated by the NO/cGMP/PKG signaling pathway . Therefore, we analyzed the phosphorylation of NF‐κB p65 subunit in the nuclear fraction of Molt‐3 cells treated with tadalafil/Sp‐8‐Br‐PET‐cGMP by Western blot analysis, which revealed that phospho‐NF‐κB p65 was downregulated by the drugs, but PKG inhibitor KT5823 (100 nM) reversed the effect (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Western blotting was performed as previously described (Zhang et al, 2017) with minor modifications. Cells were harvested and lysed using NP-40 lysis buffer (Beyotime, Shanghai, China) supplemented with protease inhibitor phenylmethanesulfonyl fluoride (PMSF), and the protein concentration was determined using a Bicinchoninic acid Protein Assay Kit (Thermo Fisher Scientific, Shanghai, China).…”
Section: Western Blottingmentioning
confidence: 99%
“…Cell samples were harvested using NP-40 cell lysis buffer 24 h post-PRRSV inoculation unless noted otherwise. Protein concentrations were determined using the Pierce BCA Protein Assay Kit (Thermo Fisher Scientific) and samples were mixed with 5× SDS sample loading buffer before samples containing equal amounts of total protein were loaded onto 12% SDS-PAGE gels and separated proteins were transferred onto PVDF membranes as described previously [36]. Membranes were probed with Mab2-5G2 or 6D10 (against the PRRSV-N protein) or anti-β-actin mAb (Abcam, Cambridge, MA, USA).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Total RNA was extracted from cells using TRizol reagent (Invitrogen, Carlsbad, CA, USA) in accordance with the manufacturer's instructions. Reverse transcription and qPCR were conducted using PrimeScript RT reagent Kit (TaKaRa) as previously described [36]. Transcripts of GAPDH were also amplified to normalize the total RNA input.…”
Section: Quantitative Real-time Pcr (Qpcr)mentioning
confidence: 99%